Predicting military innovation - Isaacson, Jeffrey A. (Jeffrey Alan), 1960-; Layne, Christopher; Arquilla, John.; Arroyo Center. Strategy and Doctrine Program; Rand Corporation; United States. Army. (Santa Monica, CA : RAND, 1999)
Although military technology is increasingly available and affordable, not all states have the capacity to improve military effectiveness by acquiring hardware. Integrative difficulties--in command structures, doctrine and tactics, training, and support--are common in the developing world, and many states will have to find some level of innovation to overcome such difficulties if they are to use military technologies effectively. This annotated briefing documents a research effort aimed at understanding and predicting how militaries may improve their battlefield effectiveness. The briefing first analyzes military innovation conceptually and then formulates a framework for predicting the likelihood of innovative success. The research synthesizes a broad literature on innovation and provides a useful tool for assessing future military developments.
"Arroyo Center."
Includes bibliographical references (p. 57-60).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Armed Forces -- Technological innovations -- Case studies; Armed Forces -- Technological innovations -- Forecasting; Chaco War, 1932-1935.; Military art and science; Israel -- Armed Forces; Vietnam (Republic) -- Armed Forces